Survey the effect of Aloevera cream on severity of radiotherapy induced ‎dermatitis in cancer patients in Razi hospital in Rasht in ‎‏2008‏‎ ‎ - mojgan Baghaie; roholah bakhshi; atefeh ghanbari; abas rahimi; zahra atrkar ruoshan (Journal of Holistic Nursing and Midwifery)
Introduction: Radiation Therapy as a cancer treatment method has special acute and late side ‎effects specially alteration in skin tissue health that needs caring with different products ‎which can have other side effects. Therefore natural products are considering decreasing side ‎effects severity.‎ Objective: This research is conducted to determine the effect of Aloevera cream on severity ‎of radiotherapy induced dermatitis in cancer patients.‎ Methods: The present research is a clinical trial study that is done on ‎‏120‏‎ cancer patients who ‎were randomly classified in ‎‏2‏‎ groups of case (‎‏60‏‎ samples using topical Aloevera cream, ‎‏35%‏‎ ‎TID until ‎‏25‏th session of treatment) and control (with Routine care). Data collection ‎instrument was a two – section questionnaire including ‎‏1‏‎) researcher – made section ‎related to personal, disease and treatment characteristics and ‎‏2‏‎) modified RTOG index to ‎assess the severity of skin reaction gathered by interview, observation and measurement of ‎patients' weight and height. By using Chi-square, it was shown that both groups were ‎matched in all variables. Data related to the second part of the tool was gathered by an ‎observer in first and ‎‏25‏th session of radiotherapy. Data were analyzed by descriptive and ‎deductive statistics by SPSS software version ‎‏14‏‎.